Life-history traits in an evergreen Mediterranean oak respond differentially to previous experimental environments (Web Ecology, 2008)
Living organisms respond both to current and previous environments, which can have important consequences on population dynamics. However, there is little experimental evidence based on long-term field studies of the effects of previous environments on the performance of individuals. We tested the hypothesis that trees that establish under different environmental conditions perform differently under similar post-establishment conditions. We used the slow-growing, evergreen Mediterranean oak Quercus ilex subsp. rotundifolia as target species. We analyzed the effects of previous environments, competition effects and tradeoffs among life-history traits (survival, growth, and reproduction). We enhanced seedling establishment for three years by reducing abiotic environmental harshness by means of summer irrigation and artificial shading in 12 experimental plots, while four plots remained as controls. Then these treatments were interrupted for ten years. Seedlings under ameliorated environmental conditions survived and grew faster during early establishment. During the post-management period, previous treatments 1) did not have any effect on survival, 2) experienced a slower above-ground growth, 3) decreased root biomass as indicated from reflectivity of Ground Penetration Radar, 4) increased acorn production mostly through a greater canopy volume and 5) increased acorn production effort. The trees exhibited a combination of effects related to acclimation for coping with abiotic stress and effects of intra-specific competition. In accordance with our hypothesis, tree performance overall depended on previous environmental conditions, and the response was different for different life-history traits. We recommend early management because it increased plot cover, shortened the time to attain sexual maturity and increased the amount of acorn production. Plots such as those assessed in this study may act as sources of propagules in deforested agricultural landscapes thus aiding natural establishment of new plants